1995
DOI: 10.1111/j.1748-0361.1995.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in Mortality Among Americans 55 Years and Older: Analysis of the National Longitudinal Mortality Study

Abstract: Previous research on rural and urban differences in risk of mortality has been inconclusive. This article used data from the National Longitudinal Mortality Study to establish whether all-cause mortality risk among persons 55 years and older varies by degree of urbanization, controlling for the potential sociodemographic confounders of age, gender, race/ethnicity, education, income, and marital status. Using the Cox Proportional Hazards Regression Procedure, the authors found that persons living in the most ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
2
30
2
Order By: Relevance
“…We are investigating this possibility in a separate analysis. Our preliminary findings are not supportive of the "artifact" explanation for urban dwellers" (Smith et al 1995). In rural areas, roads are more poorly maintained, vehicular accidents more prevalent, and emergency services are slower to respond (Wright 1985), pointing to an urban advantage in these areas.…”
contrasting
confidence: 48%
See 3 more Smart Citations
“…We are investigating this possibility in a separate analysis. Our preliminary findings are not supportive of the "artifact" explanation for urban dwellers" (Smith et al 1995). In rural areas, roads are more poorly maintained, vehicular accidents more prevalent, and emergency services are slower to respond (Wright 1985), pointing to an urban advantage in these areas.…”
contrasting
confidence: 48%
“…In rural areas, roads are more poorly maintained, vehicular accidents more prevalent, and emergency services are slower to respond (Wright 1985), pointing to an urban advantage in these areas. Smith et al (1995) also observe that the range of services available in rural areas are fewer in terms of both health care facilities and health care providers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Smith et al and Hayward et al focused on a population of men 55 years or older and found that excess mortality existed among urban residents even after controlling for differences in social class and lifestyle factors between urban and suburban residents. 12,13 Although the aforementioned studies performed adjustments for population composition and socioeconomic status, no study has yet examined how the extent of urban-suburban health disparities in a metropolitan area may be influenced by the region's built environment. The built environment, encompassing all of the buildings, spaces, and products that are created or significantly modified by people, not only forms a backcloth against which people live, work, and play, 14 but also to some degree determines residents' exposure to environmental risks and the associated physiological and psychosocial impacts.…”
Section: Introductionmentioning
confidence: 99%